Photosynthetic Potential and Productivity of Common Beans under Herbicide Effect - LIMA,G.R. (2018)
ABSTRACT: The objective of this study was to evaluate the effects of the application of contact herbicides recommended for common bean crops, as for chlorophyll a fluorescence parameters, leaf soluble proteins content (LSPC) and productivity. The experiment was conducted on the field with five treatments, which were the application of the following herbicides: bentazon (720 g ha-1), fluazifop-p-butil (187.5 g ha-1), fomesafen (250 g ha-1) fluazifop-p-butil + fomesafen (187.5 + 250 g ha-1), and a manually weeded control treatment without herbicide application, in a randomized block design with four replications. Bentazon was the only herbicide causing significant reductions, but only until the first day after herbicide application (DAA), on the following chlorophyll a fluorescence parameters: maximum quantum yield of photosystem II (Fv/Fm), effective quantum yield of photosystem II (ϕPSII), photochemical quenching (qP); it also induced an increase in non-photochemical quenching (NPQ). Fv/Fm was the best parameter to indicate herbicide effect on the photosynthetic apparatus of plants in the field. Chlorophyll a fluorescence parameters obtained in light-adapted leaves underwent a high environmental influence, especially deriving from the variation in the photosynthetic photon flow density (PPFD) during measurements; they are not recommended to evaluate the effects of herbicides on the field. None of the applied herbicides evaluated caused reductions in grain yield; therefore, they are recommended for common bean crops.